The role of TGF-ß1 in osteoarthritis of the temporomandibular joint in two genetic mouse models. (July 2016) - Long, E.; Motwani, R.; Reece, D.; Pettit, N.; Hepworth, J.; Wong, P.; Reynolds, P.; Seegmiller, R.
Highlights: The pathogenesis of temporomandibular joint (TMJ) osteoarthritis (OA) is molecular. TGF-ß1 plays a role in the molecular signaling pathway leading to TMJ OA. TGF-ß1 is accompanied by Smad2 and Htra1. Abstract: Objective: The objective of this study is to elucidate osteoarthritis (OA) progression in the temporomandibular joint (TMJ) in two genetic mouse models by assessing the expression of an identified inflammatory marker associated with OA, viz., Tgf-ß1. This study provides mechanistic insight into disease progression based on the temporal expression of Tgf-ß1 in the TMJ. Design: The two models included the heterozygous chondrodysplasia mutation ( cho/+ ), a Coll11a1 mutation, and the autosomal semidominant disproportionate micromelia mutation ( Dmm/+ ), a Col2a1 mutation. To determine OA status histologically, TMJs from each mutant were fixed, sectioned and stained with Safranin O to identify proteoglycans in condylar cartilage and counterstained with Fast Green. The extent of staining and onset of OA-like changes were quantified using the Modified Mankin scoring system. Using immunofluorescence, selected tissue sections of each genotype were stained for the presence of Tgf-ß1, HtrA1, and p-Smad2. Results: The results revealed Mankin scores of the condylar cartilage of both mutants that are consistent with established histopathological changes of OA. Immunofluorescence indicated increased expression of all three molecular markers and their co-localization within condylar chondrocytes of both mutants. Conclusions: Elevated Tgf-ß1 expression in mutant condylar cartilage supports the hypothesis that this inflammatory mediator is mechanistically involved in the pathogenesis of TMJ OA. Compared to basal expression in control TMJs, the positive co-localized staining for Tgf-ß1, HtrA1, and p-Smad2 in both mutants demonstrates involvement of these molecules in the degradative pathway of OA. Tgf-ß1 therefore is a potential target for further study for the diagnosis and treatment of TMJ OA.